Virtual Reality Architecture Oriented Wireless Connection For Future Generation Virtual Reality Devices - dhika, harry; putra, dicky kurnia (Universitas Trilogi, 2020)
In order to enhance the user experience of virtual reality (VR) devices, VR multi-user environments and wireless connections must support as the latest generation of VRdevices. Wireless network-based wireless communication devices (WLANs) are popular consumer devices with high throughput and low cost using incompatible bands. However, the use of WLANs can cause packet delivery delays, due to their distributed nature when accessing channels. In this paper, we carefully discuss wireless VR via WLAN, and we request an efficient wireless multiuser VR communication architecture, as well as providing communication for VR. Because the architecture proposed in this paper uses many WLAN standards, based on the characteristics of each VR traffic chain, it is agreed that it supports the efficient sending of massive uplink data generated by several VR devices, and provides adequate frame rates and video control frames. rate for high-quality VR services. We conduct evaluations that are supported to improve exceptional applications than are supported